(untitled) (Nepal Journal of Neuroscience, 2020)
Japanese encephalitis is an important cause of encephalitis in Southeast Asia. Survivors may suffer from various movement disorders leading to disability, presumed to be due to involvement of basal ganglia and thalamus. Oromandibular dystonia is a rare complication of Japanese encephalitis and treatment is unsatisfactory in severe cases. We report a child with JE who developed markedly severe oromandibular dystonia in subacute phase of illness. His Magnetic Resonance Imaging revealed involvement of basal ganglia and thalami. Oral antidystonic medications were used without much avail. In view of severe disabling oromandibular dystonia he was treated with botulinum toxin without adverse effects and had improved quality of life. Botulinum toxin may be considered as a therapeutic option in severe oromandibular dystonia following Japanese encephalitis.